- Stock Return: Effect Return On Equity And Debt To Equity Ratio Moderated Earning Per Share: - - Sugiono Sugiono; Abdul Halim; Djuni Farhan (Cita Konsultindo Research Center, 2023)
One of the advantages obtained from buying shares by investors is in the form of Stock Return (SR). There are many variables that can influence Stock Return (SR), including Return On Equity (ROE), Debt to Equity Ratio (DER) and Earnings Per Share (EPS). The objective of the research was to examine the partial impact of return ROE, DER, and EPS on SR and assess the role of EPS in moderating the association between ROE and DER on SR.This study uses an explanatory research approach.In 2019-2020, a total of 57 manufacturing coorporation in the consumer goods industry were listed on the Indonesia Stock Exchange. From this population, 35 companies were selected using a purposive sampling technique. To analyze the data.used analysis of moderated multiple linear regression. This study concludes that ROE, DER and EPS partially affect SR and EPS strengthens the relationship between ROE and DER on SR.